Reduction of Diesel Engine’s Particulate Matters using Retrofit CeO2 Diesel Oxidative Catalyst and Partial Flow Diesel Particulate Filter System - Hai Liu; Chinda Charoenphonphanich; Preechar Karin; Mek Srilomsak; S. Srimanosaowapak; Katsunori Hanamura (IOP Conference Series Earth and Environmental Science, 2022)
Abstract In this research, CeO2 was chosen for the DOC catalyst. Moreover, a partial-flow DPF was installed after DOC. The exhaust gas experiment was conducted at 20% - 50% engine load varying 1000,1500, and 2000 rpm of engine speed. The research results show that NOx reduced around 25% with CeO2 DOC and DPF systems at higher engine load. On the other hand, particulate matters decrease around 65% after CeO2 DOC and DPF systems. Furthermore, CO and HC amount were substantially reduced after applying after-treatment systems. According to fuel consumption, BSFC, and BTE results, the after-treatment system has no significant impact on engine performance.
Keywords: Catalytic Processes in Materials Science; Vehicle emissions and performance; Biodiesel Production and Applications